( 1 + 3 1 + 3 ⋅ 6 1 ⋅ 3 + 3 ⋅ 6 ⋅ 9 1 ⋅ 3 ⋅ 5 + ⋯ ) 2 = ?
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
How did you get the the idea the the series would exist by making first two terms equal to some value ?
We can see that the general term of expression is 2 1 × 3 n 1 × ( n 2 n ) from second term 3 1 . Any further suggestions ?
Problem Loading...
Note Loading...
Set Loading...
We know,
( 1 + x ) n = 1 + n x + 2 ! n ( n − 1 ) x 2 + 3 ! n ( n − 1 ) ( n − 2 ) x 3 + …
Now,
n x = 3 1 and 2 ! n ( n − 1 ) x 2 = 6 1
By solving the above equations, we'll get x = − 3 2 and n = − 2 1 .
Therefore, ( 1 + x ) n = ( 3 1 ) − 2 1 = 3 2 1 , so our answer is ( 3 2 1 ) 2 = 3